2019
DOI: 10.3390/ijerph16214159
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity: A Comparative Analysis between Migrant and Native Workers in Australia

Abstract: Job insecurity is a modifiable risk factor for poor health outcomes, and exposure to job insecurity varies by population groups. This study assessed if job insecurity exposure varied by migrant status and if the differences varied by gender, age, educational attainment, and occupational skill level. Data were from wave 14 of the Household Income and Labour Dynamics in Australia Survey. The outcome was job insecurity. Exposure was migrant status defined by (1) the country of birth (COB), (2) the dominant langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 48 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…The score of job insecurity was computed by summing the three items running from 3 to 21, with a higher score representing higher job insecurity (Cronbach’s α = 0.67). This scale has been shown to have good internal consistency in previous Australian studies [ 16 , 24 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 84%
See 4 more Smart Citations
“…The score of job insecurity was computed by summing the three items running from 3 to 21, with a higher score representing higher job insecurity (Cronbach’s α = 0.67). This scale has been shown to have good internal consistency in previous Australian studies [ 16 , 24 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 84%
“…In our previous studies of the same sample [ 23 ], we found that migrants from Non-English-speaking countries experience lower skill discretion than Australian-born workers even more than 11 years post-arrival in Australia, while migrants and Australian-born workers have similar decision authority. Furthermore, migrants from Non-English-speaking countries have higher job insecurity than Australian-born workers up to 11 years post-arrival [ 24 ]. In particular, highly educated migrants from Non-English-speaking countries with bachelor or postgraduate educational level experience ‘double adverse exposures’ (lower skill discretion and higher job insecurity) even after 11 years post-arrival in Australia [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations